Contribution of livestock H2S to total sulfur emissions in a region with intensive animal production. Issue 1 (December 2017) - Feilberg, Anders; Hansen, Michael; Liu, Dezhao; Nyord, Tavs
Abstract Hydrogen sulfide (H2 S) from agricultural sources is generally not included in sulfur emission estimates even though H2 S is the major sulfur compound emitted from livestock production. Here we show that in a country with intensive livestock production (Denmark), agriculture constitute the most important sulfur source category (~49% of all sources of sulfur dioxide), exceeding both the production industry and energy categories. The analysis is based on measurements of H2 S using proton-transfer-reaction mass spectrometry. National emissions are obtained using ammonia as a reference pollutant with the validity of this approach documented by the high correlation of ammonia and hydrogen sulfide emissions. Finisher pig production is the most comprehensively characterized agricultural source of sulfur and is estimated to be the largest source of atmospheric sulfur in Denmark. The implication for other locations is discussed and the results imply that the understanding and modeling of atmospheric sulfate sources should include agricultural H2 S. Hydrogen sulfide (H2 S) from agricultural sources is generally omitted from sulfur emission estimates despite its abundance in livestock emissions. Here, the authors show that agriculture is the most important source of sulfur in Denmark using proton-transfer-reaction mass spectrometry measurements of H2 S.